Designing A Culture-Based Learning Model for Sustainability: Regional Contextualization Using SEA-PLM Indicators in Indonesia and Malaysia - Yadi Kusmayadi; Wulan Sondarika; Yat Rospia Brata; Soni Ramdani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving the quality of basic education in ASEAN remains challenging despite widespread teacher training initiatives. Reports from UNESCO and ASEAN (2016–2025) highlight the lack of contextualization in educational programs, leading to weak implementation of Education for Sustainable Development (ESD) in classrooms. This study employed an Educational Design Research (EDR) approach to develop a conceptual model of culture-based learning in harmony with nature. The research was conducted in two phases. Phase 1 involved a comparative analysis of Indonesia’s Kurikulum Merdeka and Malaysia’s KSSR Semakan 2017, combined with classroom observations and interviews at two culturally significant primary schools: SD Model Aulady (Ciamis, Indonesia) and Sekolah Kebangsaan Sikuati (Sabah, Malaysia). Phase 2 focused on designing and validating a conceptual prototype integrating local wisdom—Kagaluhan (Indonesia) and Sumuku–Tagal (Malaysia)—into the SEA-PLM framework. Findings from Phase 1 revealed shared challenges, including limited pedagogical readiness, inadequate infrastructure, and weak integration of cultural and environmental content. In Phase 2, the resulting model successfully mapped local values into the four SEA-PLM domains: interconnectedness, environmental sustainability, equity and peace, and active global citizenship. The model was further supported with thematic learning materials and contextualized literacy assessments. The study demonstrates that regional contextualization through local wisdom can enhance the relevance and effectiveness of ESD implementation. The proposed model contributes to SDG 4 (Quality Education) by promoting a culturally grounded, student-centered, and sustainability-focused pedagogy for primary education across ASEAN.